Risk Factors of Computer Vision Syndrome and its Prevention - Khadeeja Imran, Maha Izzat Khan, Hafiz Muhammad Jahan Zaib, Fahmina Nazir, Nida Armoghan Khan, Amina Khalid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The 21st century is thought to need these gadgets. They are employed in households, as well as in recreational settings and educational organizations, in addition to workplaces and businesses. The term "video display terminal" is used to refer to a computer screen (VDT). It includes computers, tablets, e-readers, smartphones, and other electronic gadgets. According to estimates, 45 million employees use computers directly by gazing at VDTs nonstop for long periods. Aim: The goal of this study was to count how many CMT (college of Medical Technology) students have computer vision syndrome and to identify the risk factors that go along with it. Methods: This cross-sectional research was conducted on 198 CMT students at Pakistan institute of Medical Sciences, Islamabad, Pakistan, from 1st April 2022, to 30th September, 2022. The research covered all students between the ages of 17 and 25 who had used a computer in the month before the programs start date. Those students who were using eye medications, those with underlying systemic conditions like diabetes or hypertension, those with pre-existing eye problems, and those who did not provide informed written permission were excluded from the study. To demonstrate relationships between categorical data, the chi-square test was performed. The SPSS version 23 was used to analyze the data. Results: Age of 20.16 ± 3.81 years on average. Out of 198 respondents, 133 (67.2%) said they had at least one of the following symptoms of computer vision syndrome: headache, eye tiredness, burning, eye irritation, neck discomfort, and shoulder pain. Computer users’ eye complaints included eye irritability (48%), burning (33%), and eye weariness (15%). Extraocular symptoms range from headaches (38%) to neck and shoulder discomfort (21.8%). Computer use time (240 minutes/four hours) was substantially correlated with eye tiredness and headache. Practical Implication: The benefit of this study is to identify the risk variables linked with computer vision syndrome and its incidence among undergraduate medical students. It will aid in raising public awareness of the health risks associated with computers and other digital electronic devices, as well as assisting public health experts and other stakeholders in taking action to address this public health problem Conclusions: The ailment known as "Computer Vision Syndrome" affects a lot of young students who use computer regularly Keywords: Computer Vision Syndrome, Risk, Prevention, households, irritability, pain, eye tiredness, .